کتاب الام کا منہج ،اسلوب اور خصائص ایک تحقیقی مطالعہ: A Research study on the Methodology and characteristics of Kitaab Al-Umm - Muhammad Amaar Hasan Khan; Dr. Manzoor Ahmad (MEI, 2023)
Man is astonished to see how Allah has arranged to save Islam and its teachings. It is a miracle that a child memorizes the whole Quran without any mistake. In the same way Allah produced such personalities with remarkable memory for the preservation of Hadith, memorized millions of Hadith. Then, knowledge related the preservation of Quran & Hadith, Ilm-Asual-Deen, Asul-Fiqah, Ilm-e-Fiqah established a department of knowledge. People adopted it as a hobby to serve the mankind and considered it as a blessing for eternity to propagate it. By dint of hard work and research, they performed the labor of preservation of Quran and Hadith and its associated knowledge. Imam Shafi is among those who derived the solutions of the problems from Quran & Hadith, presented it before the Muslim Ummah and guided them. Imam Shafi arranged these commandments in the form of “Khitab-ul-Umm”. It has gained prominent place in the views of “Fukhah and Muhaddisin”. Guidance from Quran and Hadith is its main feature. All the solutions of the problems are derived from Quran & Hadith. It is a book of Hadith as well as Book of Fiqah. A person who wants to learn and research must study this book. Ullamah praised this book very much.